INDONESIAN BOND YIELDS: INFLATION, FED RATES, AND EXCHANGE RATE EFFECTS - Sany, Sany; Hatane, Saarce Elsye; Angelique, Zefanya Metanoya; Darmasaputra, Alan; Gabronino, Rosalia Taub (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This research aims to analyze the effects of Indonesian inflation, the rise of the US Fed rate, and the exchange rate on the yield of Indonesian government bonds. This study employs a quantitative approach using secondary data obtained from reliable sources, such as the Bloomberg database, the official website of Bank Indonesia, and the official website of the Federal Reserve. The sample comprises 132 months of macroeconomic rates and prices, covering 10 years from 2012 to 2022. Data analysis included descriptive statistics, classical assumption tests, and stationarity testing. While previous studies have analysed the effects of these factors on government bond prices, this study investigates explicitly their impact on government bond yield in Indonesia. The results show that inflation and the exchange rate positively affect the Indonesian government bond yield. However, the rise in the US Federal Reserve rate does not significantly drive changes in the Indonesian government bond yield.